Attitudes of Physicians, Midwives, and Nurses About Doulas: A Scoping Review. Issue 1 (January 2019) - Lucas, Laura; Wright, Erin
Abstract: Introduction: Evidence supports numerous positive clinical benefits of doula care. There are varying attitudes among physicians, midwives, and nurses toward support of doulas in a collaborative approach with women in labor. Tension and conflict with use of doulas may occur in some intrapartum settings in the United States. Methods: A scoping review of the literature between January 2008 and January 2018 was conducted using PubMed, CINAHL, Google Scholar, and Scopus database to identify specific attitudes of physicians, midwives, and nurses toward doulas; 1, 810 records were identified and initially reviewed. Inclusion criteria included original research published in the last 10 years and in the English language. Articles were excluded if the research was not original and if obstetrical providers' or nurses' attitudes toward doulas were not included. Results: Three records met criteria for inclusion. All used a cross-sectional survey design. Two were set in Canada exclusively and one was inclusive of nurses and doulas in both Canada and the United States. Themes emerged that may explain the influence and variances in attitudes toward doulas and the support they provide to laboring women. Clinical Implications: More research is needed to identify attitudes of members of the maternity care team toward doulas and to better understand implications of their attitudes on working together collaboratively and on patient outcomes. Abstract : Physicians, midwives, and labor nurses are not consistent in their willingness to work with doulas. In this review, research about attitudes of members of the maternity team towards doulas is presented, with suggestions for improved collaboration.